The Last Voice - Latorre, José Ignacio. author. aut Link
XVIII, 179 p. 4 illus., 3 illus. in color.
Keywords: Most human beings don’t manage to achieve fame. Roy J. Glauber did so for two different reasons. Glauber was not only a Nobel-Prize winning physicist, but also one of the last surviving scientists who worked in Los Alamos in the Theoretical Division of the Manhattan Project. He was a witness to all the events and knew all the scientists associated with the creation and launch of the first atomic bombs. This book is the product of a series of long interviews held with Roy over three years: in Benasque (Spain) in 2011, and later in Singapore and Cambridge (USA). Its pages give a first-hand account of a true protagonist, one who is independent, lucid, sagacious and committed to the truth. The authors have respectfully preserved his spirit: his voice is the one that matters. The authors asked the questions and they relay his answers. Their comments are confined to the footnotes and to brief explanatory paragraphs, added simply to provide certain relevant details. The importance of the events that Glauber describes here is indisputable, as therefore is the book itself. The events narrated in its pages will remain part of world history, perhaps for centuries or even millennia. We live today in the shadow of the decisions made at that time.﻿.